Physicochemical properties of hot-dog of meat of flame with incorporation of albumen, rubber of tare and protein of soy bean - Apaza, Apaza (2017)
We assessed the texture profile (TPA), Aw and PH of hot-dog elaborated on the basis of llama meat; We worked with 16 formulations that included different levels of inclusion of egg albumin (AH), Tara Gum (GT) and functional soy Concentrate (CSF). By TPA, cohesiveness, mastication, hardness, gumminess and elasticity were assessed. To evaluate the individual and synergistic effect of the components, the mixture design method was used. It was found that the addition of CSF influenced significantly in hardness (R2 = 0.92) and chewability (r2 = 0.94), while cohesiveness was positively influenced by the greater proportion of GT and AH (r2 = 0.97). On the other hand, the elasticity showed greater magnitude when the proportion of CSF and AH (R2 = 0.90) increased in the mixture. The microbiological barriers of ph and AW were also evaluated, it was observed that the Aw was reduced mainly by CSF and AH (r2 = 0.765) and ph decreased when Tara gum increased (r2 = 0.79). In the program, hardness (79,115 N) and elasticity (10,930 mm) were optimized. The three components replaced 3% of the base formulation. The optimized formula (FO) presented 14.6% AH, 16.3% of GT and 69.1% of CSF. The texture characteristics of the FO were compared with a hot dog made with pork HDCC (hardness 75.828 ± 10%, elasticity 11.470 ± 10%), and another flame HDCLL (hardness 41.830 ± 10%, elasticity 9.180 ± 10%), no significant differences were found with respect to the Elasticity. Regarding hardness, HDLL compared with HDCC showed significant differences (P < 0.05); But when 3% of the components were incorporated into the formulation of llama meat (FOCM) it did not present significant differences.